A tale of two villages: An investigation of conservation-driven land tenure reform in a Cambodian Protection Forest. (February 2015) - Travers, Henry; Winney, Kyle; Clements, Tom; Evans, Tom; Milner-Gulland, E.J.
Highlights: We analyse household land use and compliance with land use plans in two villages. Shift observed away from traditional land use towards commercial agriculture. Compliance highly correlated with total land holdings and participation in reform. Understanding of reforms greater in village with higher rates of compliance. Support for local resource management institutions required. Abstract: In this paper, we present an analysis of the change in household land use following a conservation-driven process of indigenous land titling reform in a Cambodian protected area. In each of the two study villages, we investigated how household land use had changed and the extent of compliance with both legal boundaries of titled areas and community regulations created to govern land use within these areas. A comparison of current household land holdings in each village with those at the start of the tenure reform process indicated a significant increase in household land holdings. Changing land use practices were also revealed, as households shift away from traditional subsistence based land use towards more commercialised agriculture. Household compliance was observed to be strongly correlated with total land holdings and participation in the tenure reform process, with compliance levels significantly higher in the village that had experienced lower levels of external land grabbing and immigration. Similarly, understanding and perceptions of the tenure reform process was found to differ dramatically between the two study villages. The importance of supporting local resource management institutions created through tenure reform, particularly in the face of strong external drivers of change, and of engaging with immigrant households are highlighted as key to the continuing effectiveness of participatory land use planning approaches.